Moral Discernment in History - Keenan, James F. (Theological studies, 2018)
The concept of moral discernment is often used to describe the inspired decision-making of a conscientious Christian, but Pope Francis uses it relationally in terms of accompaniment and often enough, more broadly than an individual's choice. Rather, he suggests that bishops and their local churches ought to morally discern how they should settle issues addressing contemporary pastoral challenges. This article argues that in its history, moral discernment was a social practice used in a variety of relational ways to determine a pathway for living out the summons of the gospel.